2017
DOI: 10.21037/jovs.2017.07.04
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal video-assisted thoracic surgery for pneumothorax and blebs/bullae

Abstract: Abstract:The last British Society of Thoracic Surgeons guidelines of 2010 for the management of primary spontaneous pneumothorax (PSP) stated that, after the first recurrence, the treatment of PSP should be a surgical operation, like a bullectomy accompanying with a procedure for inducing pleural adhesions. Therefore, the surgical approach is considered the best treatment to minimise the risk of recurrence in patients who experienced a PSP. There is substantial evidence in the literature demonstrating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…It has been observed that different lesions have different gene expressions, the main site could have EGFR positive expression, while metastasis not. Moreover; metastasis in different sites of the body might be a different cancer as it has been observed in previous case reports 12, 13. Usually adenocarcinoma tends to transform to small cell lung cancer either due to tyrosine kinase inhibitors or on its own due to a cascade of inflammatory proteins that are secreted from the tumor 14-16.…”
Section: Introductionmentioning
confidence: 79%
“…It has been observed that different lesions have different gene expressions, the main site could have EGFR positive expression, while metastasis not. Moreover; metastasis in different sites of the body might be a different cancer as it has been observed in previous case reports 12, 13. Usually adenocarcinoma tends to transform to small cell lung cancer either due to tyrosine kinase inhibitors or on its own due to a cascade of inflammatory proteins that are secreted from the tumor 14-16.…”
Section: Introductionmentioning
confidence: 79%
“…[5] An acceptable rate of recurrence, better patient satisfaction, and improved tolerability are shown in the VATS technique. [4] In this method, conventional two-or three-port approaches are preferred. The SP approach has emerged as an alternative to the traditional method.…”
Section: Discussionmentioning
confidence: 99%
“…The key to success in the uniportal approach is the use of an angled (30º) thoracoscope and staplers with articulation. [4,11,13] Also, the intercostal space is required to be dissected widely so that the extensive mobility of all instruments can be ensured. Therefore, the size of the intercostal opening should be much larger than the skin incision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an historical view, world famous anesthesiologists and thoracic surgeons gave their marvelous contributions to the development of this relatively new "exciting" surgical approach in thoracic surgery (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Uniportal Single Incision Vats For the Skepticsmentioning
confidence: 99%